System analysis based on the migration- and invasion-related gene sets identifies the infiltration-related genes of glioma - Shi, Shuang; Zhong, Jiacheng; Peng, Wen; Yin, Haoyang; Zhong, Dong; Cui, Hongjuan; Sun, Xiaochuan (Frontiers in Oncology, 2023)
The current database has no information on the infiltration of glioma samples. Here, we assessed the glioma samples' infiltration in The Cancer Gene Atlas(TCGA) through the single-sample Gene Set Enrichment Analysis(ssGSEA) with migration and invasion gene sets. The Weighted Gene Co-expression Network Analysis (WGCNA) and the differentially expressed genes(DEGs) were used to identify the genes most associated with infiltration. Gene Ontology(GO) and the Kyoto Encyclopedia of Genes and Genomes(KEGG) were used to analyze the major biological processes and pathways. Protein-protein network interaction analysis (PPI) and the least absolute shrinkage and selection operator (LASSO) were used to screen the key genes. Furthermore, the nomograms and receiver operating characteristic curve(ROC) were used to evaluate the prognostic and predictive accuracy of this clinical model in patients in TCGA and the Chinese Glioma Genome Atlas(CGGA). The results showed that turquoise was selected as the hub module, and with the intersection of DEGs, we screened 104 common genes. Through LASSO regression, TIMP1, EMP3, IGFBP2, and the other 9 genes were screened mostly in correlation with infiltration and prognosis. EMP3 was selected to be verified in vitro. These findings could help researchers better understand the infiltration of gliomas and provide novel therapeutic targets for the treatment of gliomas.